Citizens’ Right to Privacy and Right to Information Access in Smart Cities: Evaluating the Smart City Initiative of West Baltimore - Park, Sunyup (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
This paper will detail smart city initiatives in West Baltimore and evaluate different approaches to ensure the right to privacy and the right to information access of lower-income communities of color. After evaluating these approaches, this paper proposes recommendations to facilitate the right to privacy and the right to information access in lower-income communities.